Diarrhea due to Cyclospora-like organism in an immunocompetent patient - Mairelina Marín-Leonett; Lourdes Figuera; Anaibeth Nessi; Carmen Guzmán; Patricia Torres; Linda Genzlinger; Geraldine Saavedra; Ynés R. Ortega (Journal of Infection in Developing Countries)
Cyclospora cayetanensis infection continues to be a major cause of diarrhea particularly in immunosuppressed patients. The emergence of new related parasite pathogens, is an issue of public health concern. We report here a case where a Cyclosporalike organism was the cause of diarrhea in an immunocompetent patient from Venezuela.